NLR (neutrophil to lymphocyte ratio), PLR (platelet to lymphocyte ratio), and SII (systemic immune-inflammation index) reflect disease activity and renal remission in patients with lupus nephritis - Zhang, Xiaohui; Chen, Yuan; Fan, Yong; Gao, Dai; Zhang, Zhuoli (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the value of NLR (neutrophil to lymphocyte ratio), PLR (platelet to lymphocyte ratio), and SII (systemic immune-inflammation index) in reflecting disease activity and induction therapy remission in patients with lupus nephritis (LN).MethodsActive LN patients from STAR cohort were enrolled. We analyzed the trends of complete blood count parameters with Generalized Estimated Equation. Bivariate correlation analyses, Chi-square tests, t-tests and logistic regression were employed to assess variable associations and identify prognostic factors for LN remission.Results310 active LN patients were enrolled in the study. All patients had active lupus with SLEDAI-2K 17.1 ± 6.1, median 24h-Urine Protein (UTP) level of 3.1 (1.5, 5.4) g. During the 12-month follow-up of induction therapy, NLR and PLR showed a decreasing trend. Both baseline NLR and SII were positively correlated with baseline UTP and serum creatinine (SCr) levels (r = 0.112-0.148, p< 0.05 for all). Patients with hematuria [4.8 (3.1, 8.1) vs. 4.0 (2.6, 6.5), p = 0.024] and pyuria [5.4 (3.4, 8.8) vs. 3.8 (2.6, 6.6), p < 0.001] had significantly higher baseline NLR. 159 (51.3%) patients performed kidney biopsy, and baseline NLR and SII were positively correlated with the activity index (AI) score of renal pathology (NLR: r = 0.244, p=0.013; SII: r = 0.199, p=0.043). Furthermore, the changes of NLR and SII were also positively correlated with changes in UTP and SCr during 6 and 12 months (r = 0.143-0.175, p<0.05 for all). Nevertheless, neither of baseline NLR, PLR, or SII could predict renal remission at 6 months.ConclusionOur findings suggested that NLR and SII were valuable indicators of disease activity in LN, correlating with UTP, SCr and AI score of renal pathology. NLR, PLR and SII provided us a quick, simple and cost-effective supervision way in monitoring and managing LN patients.